The domestication of Foucault: Government, critique, war. (December 2014) - Allen, Ansgar; Goddard, Roy
Though Foucault was intrigued by the possibilities of radical social transformation, he resolutely resisted the idea that such transformation could escape the effects of power and expressed caution when it came to the question of revolution. In this article we argue that in one particularly influential line of development of Foucault's work his exemplary caution has been exaggerated in a way that weakens the political aspirations of post-Foucaldian scholarship. The site of this reduction is a complex debate over the role of normativity in Foucaldian research, where it has been claimed that Foucault's genealogical approach is unable to answer the question ' Why fight? ' The terms of this debate (on the neo-Foucaldian side) are limited by a dominant though selective interpretation of Foucault's analytics of power, where power is understood primarily in terms of government, rather than struggle. In response we suggest that if we reconfigure power-as-government to power-as-war, this adjusts the central concern. ' Why fight? ' becomes replaced by the more immediate question, ' How fight? ' Without denying the obvious benefits of cautious scholarly work, we argue that a reconfiguration of Foucault's analytics of power might help Foucaldian research to transcend the self-imposed ethic of political quietism that currently dominates the field.